Strategy for controlling tourist mobility: analysis of the biopolitical processes of territorialization implemented by the cruise tourism industry in a Caribbean destination - Luc Renaud (Via@)
The deployment of cruise tourism in a destination leads to the production of a space of cruise tourism through a process involving the reterritorialization of everyday spaces. To meet the prerogatives of its business model, the cruise tourism industry develops this new space by mobilizing biopolitical processes stemming from strategies of territorial control over the mobility of both tourists and local tourism stakeholders. Using a quantitative methodology and a model of tourism space that takes into account 16 zones produced by the territorialization of the everyday spaces of receiving communities, this study proposes a detailed understanding of the discursive and material strategies implemented by the cruise tourism industry to ensure control over the space it occupies. It discusses how local communities undertake the management of their territory through the exercise of a democratic, “bottom-up” biopower.